2006
DOI: 10.1063/1.2400027
|View full text |Cite
|
Sign up to set email alerts
|

Magic alkali-fullerene compound clusters of extreme thermal stability

Abstract: The thermal stability of free pure C60-, as well as C60-alkali, and -alkaline-earth metal compound clusters is investigated. We find that small (C60)m-clusters (m⩽6) decay at comparatively low temperatures below 400K, as a consequence of weak intermolecular van der Waals interaction. Adding barium or potassium to the clusters dramatically increases the decay temperatures for “magic” configurations of (C60)mBa2m−1 and (C60)mK2m, which reach values as high as 1780K. Contrary to common belief, the superstable com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…Previously, we have demonstrated that the thermal stability of C 60 clusters can be significantly enhanced by adding alkali or alkaline-earth metal atoms, thus forming superstable metalO(C 60 ) m compound clusters. 1 Whereas the decay temperatures for (C 60 ) 2 , (C 60 ) 3 , and (C 60 ) 4 were found to be 189, 270, and 340 K, respectively, much higher annealing temperatures could be reached via addition of K or Ba. Figure 1 illustrates the effect of the temperature of the heating cell on the mass spectra of Ba n (C 60 ) m clusters (in all cases the cooling cell was maintained at 150 K).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we have demonstrated that the thermal stability of C 60 clusters can be significantly enhanced by adding alkali or alkaline-earth metal atoms, thus forming superstable metalO(C 60 ) m compound clusters. 1 Whereas the decay temperatures for (C 60 ) 2 , (C 60 ) 3 , and (C 60 ) 4 were found to be 189, 270, and 340 K, respectively, much higher annealing temperatures could be reached via addition of K or Ba. Figure 1 illustrates the effect of the temperature of the heating cell on the mass spectra of Ba n (C 60 ) m clusters (in all cases the cooling cell was maintained at 150 K).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have pointed out that simple geometric and electronic shell-filling arguments may not be generally applicable to determine which clusters are magic. 1,2 In a recent communication on metalfullerene clusters we have demonstrated that the experimental setup drastically affects the observed cluster distribution. 1 In the experiments of Martin et al, 7,8 the clusters were produced in a low-pressure, inert gas condensation cell cooled by liquid nitrogen.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One or two additional A + ions are needed to provide for the net charge of the "magic" mono-and dications. However, a different pattern was observed in a later study of C 60 -potassium complexes by the MPI group [7,8]. By thermalizing the neutral precursors in helium at 900 K, subsequent cooling and soft single-photon ionization the researchers inferred that neutrals with the composition (C 60 K 2 ) m (m = 2, 3, 4) are extremely stable.…”
Section: Introductionmentioning
confidence: 97%